MOTIVASI, MINAT DAN PENGALAMAN PETANI PADA PENUMBUHAN DAN PEMBENTUKAN KELOMPOK TANI REGULER DAN KOMODITAS DI WILAYAH KABUPATEN GUNUNGKIDUL - Munanto, Totok Sevenek (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2016)
This research aims: 1) To know the motivation, interests, experiences of farmers in the growth and formation of farmer groups. The results of the research aspects of motivation is 81% of the farmers choose the regular farmers groups and the rest choose commodities. Aspects of a select group of regular farmers interest as much as 80% and the rest of a select group of commodities. The experiential aspect of farming 82% of farmers chose regular group and the rest of a select group of commodities. The general conclusion from this study is that most farmers above 80% choose regular group is a group of farmers who manage various commodities for reasons more efficiently.